Penerapan Pendekatan TaRL Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas I SD - Busnang, Yuliawati; Patta, Rahmawati; Suparti, Suparti (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
The aim of this research is to describe the application of the TaRL approach in grade 1 mathematics subjects at SD Inpres Mangasa 1, Makassar City. This research is based on one of the applications of differentiated learning, namely that it is known that students' characteristics and learning styles are different, so learning is needed that suits the needs of each student. The method used in this research is descriptive and qualitative. This research aims to describe differentiated learning using the TaRL (Teaching at The Right Level) approach. The subjects of the research were all Class 1 students of SD Inpres Mangasa 1 Makassar City. The research results show that the "Teaching at the Right Level" (TaRL) approach using a cooperative learning model and "mystery box" learning media, PowerPoint and learning videos can be used by all students with three different learning styles.